Facile preparation of hierarchically porous carbons from metal-organic gels and their application in energy storage - Xia, Wei (Nature Publishing Group, 2013)
Porous carbon materials have numerous applications due to their thermal and chemical stability, high surface area and low densities. However, conventional preparing porous carbon through zeolite or silica templates casting has been criticized by the costly and/or toxic procedure. Creating three-dimensional (3D) carbon products is another challenge. Here, we report a facile way to prepare porous carbons from metal-organic gel (MOG) template, an extended metal-organic framework (MOF) structure. We surprisingly found that the carbon products inherit the highly porous nature of MOF and combine with gel's integrated character, which results in hierarchical porous architectures with ultrahigh surface areas and quite large pore volumes. They exhibit considerable hydrogen uptake and excellent electrochemical performance as cathode material for lithium-sulfur battery. This work provides a general method to fast and clean synthesis of porous carbon materials and opens new avenues for the application of metal-organic gel in energy storage.